An updated structural model of the A domain of the Pseudomonas putida XylR regulator poses an atypical interplay with aromatic effectors. (16th June 2021) - Dvořák, Pavel; Alvarez‐Carreño, Carlos; Ciordia, Sergio; Paradela, Alberto; de Lorenzo, Víctor
Summary: A revised model of the aromatic binding A domain of the σ 54 ‐dependent regulator XylR of Pseudomonas putida mt‐2 was produced based on the known 3D structures of homologous regulators PoxR, MopR and DmpR. The resulting frame was instrumental for mapping a number of mutations known to alter effector specificity, which were then reinterpreted under a dependable spatial reference. Some of these changes involved the predicted aromatic binding pocket but others occurred in distant locations, including dimerization interfaces and putative zinc binding site. The effector pocket was buried within the protein structure and accessible from the outside only through a narrow tunnel. Yet, several loop regions of the A domain could provide the flexibility required for widening such a tunnel for passage of aromatic ligands. The model was experimentally validated by treating the cells in vivo and the purified protein in vitro with benzyl bromide, which reacts with accessible nucleophilic residues on the protein surface. Structural and proteomic analyses confirmed the predicted in/out distribution of residues but also supported two additional possible scenarios of interaction of the A domain with aromatic effectors: a dynamic interaction of the fully structured yet flexible protein with the aromatic partner and/or inducer‐assisted folding of the A domain.